Barrier Effects of Borders: Implications for BorderCrossing Infrastructures - Rietveld, Piet (European Journal of Transport and Infrastructure Research, 2012)
Borders discourage spatial interaction. The present paper gives a typology of possible backgrounds of such barriers. Five distinct ways of measuring border effects are presented and empirical results are shown for various transport modes: car, bus (public transport), train, plane. Border effects tend to decline in Europe, but they remain substantial, reductions of up to 80% are observed. They lead among others to low supply of border crossing transport links. A social cost benefit analysis of investments in international corridors is given. We find that border effects due to low demand for cross- border transport will lead to low net benefits of such investments. But the common practice that benefits of foreign users are ignored in social cost benefit analysis deserves to be reconsidered. By interpreting an international project as a joint project the benefits of foreign users are no longer overlooked, thus reducing the risk of underinvestment in international links.